(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2026)
India’s EdTech industry has rapidly evolved into a global leader, transforming the educational landscape for over 400 million learners, including 40 million students in higher education. The COVID-19 pandemic significantly accelerated the adoption of digital learning platforms, highlighting both their potential and limitations. While EdTech platforms offer substantial opportunities for enhancing student engagement, improving learning outcomes, and fostering entrepreneurial aspirations, their widespread implementation continues to face challenges such as the digital divide, limited accessibility, inadequate infrastructure, and parental concerns. This study critically examines the impact of EdTech adoption on student engagement, academic performance, and entrepreneurial orientation within India’s digital education ecosystem. A mixed-methods research design is employed, combining quantitative surveys and qualitative interviews. The study surveys 471 students from K–12 and higher education institutions across metropolitan and semi-urban regions of India, along with 25 EdTech entrepreneurs and 15 operational managers from leading firms. Secondary data from government reports, industry whitepapers, and academic literature further support the analysis. Descriptive statistics are used to identify adoption trends, while multiple linear regression assesses the relationship between EdTech usage and student engagement. T-tests and ANOVA examine demographic differences in engagement levels. Additionally, Partial Least Squares–Structural Equation Modelling (PLS-SEM) explores causal relationships among digital accessibility, AI-driven personalization, gamification, learning outcomes, entrepreneurial aspirations, and student engagement. Preliminary findings indicate a strong positive correlation between EdTech usage and improved motivation, engagement, academic performance, and retention rates compared to traditional e-learning models. The study also anticipates increased student interest in EdTech-driven entrepreneurship. The research concludes with strategic recommendations to bridge digital accessibility gaps, enhance AI-based personalization, address parental concerns, and integrate entrepreneurial learning frameworks to empower the next generation of digital entrepreneurs.